2016
DOI: 10.1186/s40337-016-0116-0
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of media literacy in eating disorder risk factor research: psychometric properties of six measures

Abstract: BackgroundEvaluation of media literacy-based interventions for the prevention of eating disorder risk is limited by the lack of appropriate measures with established psychometric properties with which to assess change in media literacy. This study aims to fill this gap by examining the psychometric properties and use in eating disorders risk factor research of six measures of media literacy that assess media processing and critical thinking about general media and critical thinking about appearance-focused med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
0
14
1
1
Order By: Relevance
“…Measures of correlates of body image were internalisation of the thin‐ideal (Schaefer et al, ), upward appearance comparison (O'Brien et al, ), appearance conversations (Jones, Vigfusdottir, & Lee, ), fear of fat (Goldfarb, Dykens, & Gerrard, ), and fear of negative appearance evaluation (Lundgren, Anderson, & Thompson, ). Media literacy variables were realism scepticism and critical thinking about appearance focused media (McLean, Paxton, & Wertheim, ).…”
Section: Methodsmentioning
confidence: 99%
“…Measures of correlates of body image were internalisation of the thin‐ideal (Schaefer et al, ), upward appearance comparison (O'Brien et al, ), appearance conversations (Jones, Vigfusdottir, & Lee, ), fear of fat (Goldfarb, Dykens, & Gerrard, ), and fear of negative appearance evaluation (Lundgren, Anderson, & Thompson, ). Media literacy variables were realism scepticism and critical thinking about appearance focused media (McLean, Paxton, & Wertheim, ).…”
Section: Methodsmentioning
confidence: 99%
“…Perceived realism of media images was assessed with the two item version of the Realism subscale of the Media Attitudes Questionnaire (Irving et al 1998;McLean et al 2015). Participants responded to items "Normally women (in real life) look like models in ads" and "Normally women (in real life) are as thin as the models in ads" on a 5-point scale from 1 (completely disagree) to 5 (completely agree).…”
Section: Independent Variablesmentioning
confidence: 99%
“…The Media Attitudes Questionnaire (MAQ; Irving et al, 1998) was adapted to assess media literacy in relation to the tanned ideal. McLean et al (2016) assessed the psychometric properties of the MAQ using exploratory and confirmatory factor analyses to address the inconsistent use of the scale in other research and found the best-fitting model included eight items (see Table 1). Items are rated on a Likert-type scale ranging from 1 ( completely disagree ) to 5 ( completely agree ).…”
Section: Methodsmentioning
confidence: 99%
“…The items are reverse-scored and a mean score calculated, with high scores indicating greater skepticism about media and a higher level of media literacy. McLean et al (2016) reported high internal consistency for scores on the MAQ subscales (α = .80–.83). Internal consistency in this study for mean scores on the MAQ was α = .74.…”
Section: Methodsmentioning
confidence: 99%